Design and Analytical Study of Strays-Insensitive Switched-Capacitor Filters - Umesh Kumar (Active and Passive Electronic Components)
Use of analog circuit elements in active networks have become very common and the demand for their miniaturization is increasing day by day. Though several methods are available for the miniaturization of these elements through large scale integration on single chips, the performance is not very satisfactory in low-frequency applications, due to the presence of parasitic capacitance that is comparable to the capacitance of active elements. As a result, the desired response gets deviated and also noise is involved. In this paper, an attempt has been made to devise methods for the elimination or reduction of the influence of these parasitic capacitances on filter circuits.